Phasers on stun! : how the making (and remaking) of Star Trek changed the world - Britt, Ryan (Plume, an imprint of Penguin Random House LLC, 2022)
"Written with inside access, comprehensive research, and a down-to-earth perspective, Phasers on Stun! chronicles the entire history of Star Trek, revealing that its enduring place in pop culture is all thanks to innovative pivots and radical change. For over five decades, the heart of Star Trek's pro-science, anti-racist, and inclusive messaging has been its willingness to take big risks. Across thirteen feature films, and twelve TV series--including five shows currently airing or in production--the brilliance of Star Trek is in its endless ability to be rethought, rebooted, and remade. Author and Star Trek expert Ryan Britt charts an approachable and entertaining course through Star Trek history; from its groundbreaking origins amid the tumultuous 1960s, to its influence on diversifying the space program, to its contemporary history-making turns with LGBTQ+ representation, this book illuminates not just the behind-the-scenes stories that shaped the franchise but the larger meaning of the Final Frontier. Featuring over 100 exclusive interviews with actors and writers across all the generations, including Walter Koenig, LeVar Burton, Dorothy Fontana, Brent Spiner, Ronald D. Moore, Jeri Ryan, and many more, Britt gets the inside story on all things Trek, like Spock's evolution from red devil to the personification of logical empathy, the near failure to launch of The Next Generation in 1987, and how Trekkie outrage has threatened to destroy the franchise more than once. The book also dives deep with creators like Michael Chabon (co-creator of Star Trek: Picard) and Nicholas Meyer (director, The Wrath of Khan). These interviews extend to the bleeding edge of contemporary Star Trek, from Discovery to Picard to Lower Decks, and even the upcoming highly anticipated 2022 series, Strange New Worlds. For fans who know every detail of each Enterprise bridge, to a reader who has never seen a single minute of any Star Trek, this book aims to entertain, inform, and energize. Through humor, insight, archival research, and unique access, this journey through the Star Trek universe isn't just about its past but a definitive look at its future." --